Empowering Rural Communities through Participatory Action Research: A Case Study of the Babadan Community’s Development in Education, Economy, and Environment - Jauhari, Moh. Irmawan; Taufiqurrohman, Ahmad (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This paper presents the results of a community service project implemented in Babadan, a rural community, using the Participatory Action Research (PAR) methodology to foster sustainable development across multiple domains: education, economic empowerment, and environmental sustainability. The project engaged community members in every stage, from problem identification to action implementation and evaluation, ensuring that solutions were context-specific and locally owned. The educational initiatives led to a 75% improvement in literacy rates and a 20% increase in school enrollment, particularly among marginalized groups. Economic empowerment efforts resulted in the creation of over 30 small businesses, with a 15% increase in household income. Environmental sustainability was achieved through the adoption of sustainable farming practices and the establishment of rainwater harvesting systems, contributing to reduced environmental degradation and improved agricultural productivity. Although the project demonstrated significant success, challenges remain in scaling businesses and ensuring long-term market access. The paper concludes with recommendations to further strengthen market linkages, financial literacy, and local leadership, while ensuring continued community engagement and external partnerships for long-term sustainability.